Karakteristik Biofisik Ruang Terbuka Hijau Pada Hutan Kota Samarinda, Provinsi Kalimantan Timur - Endayani, Sri; Sadono, Ronggo; Kusumandari, Ambar; Hartono, Hartono (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Population growth and economic activity always require space. Physical, social and economic composition always changes due to spatial land use. Changes in spatial land use that do not take into account the biophysical balance will result in natural disasters. Urban problems in the use of space result in the disturbance of the harmony between human and the nature. The economy is improving, but the nature is suffering from damages. Green open space is the right solution. This research’s objective is to determine the biophysical characteristics (soil characteristics, stand potential, slope and rainfall) of the urban forests in Samarinda. The results show the class of clay texture, acid soil pH, low organic matter and gray brown color. The urban forests in Samarinda are dominated by species of Jati (Tectona grandis), Jati Putih (Mangifera indica), Mahoni (Swietenia macrophylla), Jambu (Anacardium occidentale), Jambu Batu (Psidium guajava), Kayu Jawa (Lannea grandis), Gmelina arborea, Angsana (Pittocarpus indicus), Bitti (Vitex cofassus), Trembesi (Samania samania), Morinda citrifolia and Kapuk (Ceiba Pentandra), hilly slopes, rather steep altitude range of 16-65 mdpl and an average rainfall of 1 095.9 mm/year.